Chronic Mountain Sickness in Cattle - Cuba Caparó, Alberto (1955)
A study of Mountain Sickness is made in three highly bred Brown Swiss calves born at 4,000 meters above sea level and also in one imported Holstein cow which carried to 3,500 meters above sea level. The observations made in this study in refference to the findings hematological and anatomo pathological picture, corroborate findiungs made by Glover and Newsom. As original observations are pointed the hipertrophy, hiperplasia, necrosis and hemorrhage of the adrenal glands, atrophy of linfoid tissue, degenerative lesions of myocardial fibers and blood corpuscles values.